MAGED2 Depletion Promotes Stress-Induced Autophagy by Impairing the cAMP/PKA Pathway - Nasrah, Sadiq; Radi, Aline; Daberkow, Johanna K.; Hummler, Helmut; Weber, Stefanie; Seaayfan, Elie; Kömhoff, Martin (International journal of molecular sciences, 2023)
Melanoma-associated antigen D2 (MAGED2) plays an essential role in activating the cAMP/PKA pathway under hypoxic conditions, which is crucial for stimulating renal salt reabsorption and thus explaining the transient variant of Bartter’s syndrome. The cAMP/PKA pathway is also known to regulate autophagy, a lysosomal degradation process induced by cellular stress. Previous studies showed that two members of the melanoma-associated antigens MAGE-family inhibit autophagy. To explore the potential role of MAGED2 in stress-induced autophagy, specific MAGED2-siRNA were used in HEK293 cells under physical hypoxia and oxidative stress (cobalt chloride, hypoxia mimetic). Depletion of MAGED2 resulted in reduced p62 levels and upregulation of both the autophagy-related genes (ATG5 and ATG12) as well as the autophagosome marker LC3II compared to control siRNA. The increase in the autophagy markers in MAGED2-depleted cells was further confirmed by leupeptin-based assay which concurred with the highest LC3II accumulation. Likewise, under hypoxia, immunofluorescence in HEK293, HeLa and U2OS cell lines demonstrated a pronounced accumulation of LC3B puncta upon MAGED2 depletion. Moreover, LC3B puncta were absent in human fetal control kidneys but markedly expressed in a fetal kidney from a MAGED2-deficient subject. Induction of autophagy with both physical hypoxia and oxidative stress suggests a potentially general role of MAGED2 under stress conditions. Various other cellular stressors (brefeldin A, tunicamycin, 2-deoxy-D-glucose, and camptothecin) were analyzed, which all induced autophagy in the absence of MAGED2. Forskolin (FSK) inhibited, whereas GNAS Knockdown induced autophagy under hypoxia. In contrast to other MAGE proteins, MAGED2 has an inhibitory role on autophagy only under stress conditions. Hence, a prominent role of MAGED2 in the regulation of autophagy under stress conditions is evident, which may also contribute to impaired fetal renal salt reabsorption by promoting autophagy of salt-transporters in patients with MAGED2 mutation.